The Thief Lord - Funke, Cornelia Caroline; Latsch, Oliver (New York : Scholastic, 2003)
Escaping the aunt who wants to adopt only one of them, two orphaned brothers run away from Hamburg to Venice, finding shelter with a gang of street children and their leader, the thirteen-year-old "Thief Lord," while also eluding the detective hired to return them to Germany.
G4
Keywords: Runaways -- Fiction; Robbers and outlaws -- Fiction; Brothers -- Fiction; Detectives -- Fiction; Orphans -- Fiction; Street children -- Fiction; Venice (Italy) -- Fiction; Italy -- Fiction